Sex pheromone of horse-chestnut leafminer Camneraria ohridella and its use in a pheromone-based monitoring system - Kalinová, B; Svatos, A; Kindl, J; Hovorka, O; Hrdý, I; Kuldová, J; Hoskovec, M (Journal of chemical ecology, 2003)
Gas chromatography combined with electroantennographic detection (GC-EAD), electroantennography (EAG), and wind-tunnel and field experiments were used to reinvestigate the composition of Cameraria ohridella (Lepidoptera, Gracillariidae, Lithocolletinae) sex pheromone. The GC-EAD experiments showed one EAD-active area corresponding to the major pheromone component. (8E,10Z)-tetradeca-8,10-dienal. The EAG experiments proved that (9E)-tetracedecenal and stereoisomers of (8E,10Z)-tetradeca-8,10-dienal exhibited significant electrophysiological activity and could, therefore, be considered as possible minor pheromone components. However, wind-tunnel and field experiments demonstrated that none of these compounds affect the efficacy of the main pheromone component. A monitoring system based on (8E,10Z)tetradeca-8,10-dienal was developed and used to study the flight activity of C. ohridella.
Keywords: sexuální lákadla; stereoizomerie; Electrophysiology; Population Dynamics; Flight, Animal; Environmental Monitoring; Sex Attractants; elektrofyziologie; zvířata; Stereoisomerism; populační dynamika; monitorování životního prostředí; Chromatography, Gas; vítr; Wind; Lepidoptera; let zvířat; Animals; chromatografie plynová